Implementation of Problem-Based Learning Model and Its Effect on Students’ Physics Learning Outcomes - Soamole, Ayu Swasti Dayuni; Arafah, Kaharuddin; Subaer, Subaer (Universitas Muhammadiyah Makassar, 2023)
This study aims to implement a problem-based learning model and to measure its effect on students' physics learning outcomes. This research is a pre-experiment using a one-group pretest-posttest research design. The population in this study were all students in class XI MIPA at SMA Negeri 1 Wangi-Wangi for the 2022/2023 academic year, while the sample was 35 students who were selected using the Slovin method. The results of the descriptive analysis showed that the average score of students' physics learning outcomes before using the problem-based learning model was 7.26. Conversely, after using the problem-based learning model, the average score of students' physics learning outcomes was 12.14. The results of the N-gain test analysis showed N = 0.36, which indicated that there was an increase in students' physics learning outcomes after using the problem-based learning model. Therefore, this study concluded that the problem-based learning model is effective in improving the physics learning outcomes of class XI MIPA students at SMA Negeri 1 Wangi-Wangi.